2018
DOI: 10.1002/dc.23893
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of diagnostic performance of pathologists by reducing the number of pathologists responsible for thyroid fine needle aspiration cytology: An institutional experience

Abstract: Reducing the number of pathologists responsible for diagnostic thyroid FNA cytology resulted in a higher utilization rate of TBSRTC, and more rapid and accurate diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In this regard, Hashimoto's thyroiditis seems to be one of the most common reasons for FP calls 45,46 . Seok et al 47 suggested that reducing the number of pathologists responsible for thyroid cytopathology leads to improved diagnostic accuracy, including the lowering of FP cases.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Hashimoto's thyroiditis seems to be one of the most common reasons for FP calls 45,46 . Seok et al 47 suggested that reducing the number of pathologists responsible for thyroid cytopathology leads to improved diagnostic accuracy, including the lowering of FP cases.…”
Section: Discussionmentioning
confidence: 99%
“…In a study in which preparations diagnosed as follicular lesions were examined by 4 different pathologists, a moderate to significant evaluation difference was detected among the pathologists (9). Seok et al found that, with examination of thyroid FNAB by thyroid speialistc cytopathologists, more accurate results could be obtained in a shorter time (10).…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck surgeons working at five other hospitals without a paper on CNB were contacted to obtain information on their use of CNB, and they confirmed that they rarely used CNB in clinical settings. Therefore, data from 14 papers [30,[32][33][34][35]41,46,[48][49][50]52,54,56,57] published by authors from eight hospitals favoring CNB were compared to data from 10 papers [25,28,29,37,38,43,45,47,53,60] published by authors from six hospitals that did not favor CNB to identify differences in the proportions of diagnoses according to the TBSRTC. Fig.…”
Section: Differences In the Proportions Of Diagnoses On Consecutive Fmentioning
confidence: 99%